PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP BRAND IMAGE DAN PURCHASE INTENTION NIKE INCORPORATION DI INDONESIA PADA PENGGUNA INSTAGRAM DENGAN STRUCTURAL EQUATION MODELING - Novinda Bahniar; Erni Martini (SOSIOHUMANITAS, 2020)
Along with the growth and evolution of internet usage, Electronic Word of Mouth has become an important phenomenon for marketers and consumers alike. Electrononic word of mouth is often found in comments, posts, and likes on social media. eWOM, will affect the views of its consumers, also affect asking consumers for their products. The purpose of this study was to determine the effect of Electronic Word of Mouth on Nike Instagram on product Brand Image, and its effect on consumer Purchase Intention. This research is a quantitative study with a sample of all people who have seen comments, likes, and submissions about Nike on Instagram. The research instrument used was a questionnaire analyzed using the structural equation modeling method. Electronic Word of Mouth, Brand Image, and Purchase Intention obtain a very good response from respondents. The direct effect of eWOM on Purchase Intention is 56.5% and the effect is indirect, namely through the Brand Image is 15.8%. The effect of Electronic Word of Mouth on Brand Image is 76.5% and the effect of Brand Image on Purchase Intention has a value of 20%. Respondents considered that through a good Nike Brand Image obtained from Electronic Word of Mouth processes, it would be easier for them to have the intention of buying Nike products. Nike is advised to continue to improve Brand Image utilization which is the variable with the highest response for the effectiveness of this process